Statistik demografi Dolichotetranychus floridanus Banks pada dua kultivar nanas (Ananas comosus (L.) Merr.) - Ariffatchur Fauzi; Santoso, Sugeng; Ali Nurmansyah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Pineapple is one of important fruit crops in Indonesia. One of important problems in pineapple production is pest infestation.. This study aims to investigate the biology, demography, and life cycle of Dolichotetranychus floridanus Banks on two pineapple cultivars (Queen and Cayenne). Observation of mite development (eggs-adults) were conducted every 6 hours. Adults were observed everyday to record the fecundity. The life table was constructed from the survivor and fecundity of D. floridanus. Based on this table, the variables of population growth, including gross reproduction rate (GRR), net reproductive rate (R0), mean generation time (T) and increase intrinsic rate (r) were determined. The results showed that the GRR, R0, and r of D. floridanus in the Queen cultivar were higher than Cayenne cultivar, while the T in the Queen cultivar was lower. Queen cultivar more suitable for D. floridanus than Cayenne cultivar.